Business attachment with Top Parking Pte Ltd. - Ng, Yen Yen. (2009)
This report provides a summary of my business training experience in Top Parking Pte Ltd during my ten weeks of attachment. From the ten weeks of observation and experience of the Company's culture and practices, some conclusions and recommendations have been made. The organisation form of the Company is more mechanistic than organic. Instead of remaining this way, it is recommended that the organisation adopts the ambidextrous approach to achieve both innovation and efficiency. Based on the rites and ceremonies and the visible artifacts present in the Company, its culture is concluded to be relatively open and participative.